Phosphinic acids: current status and potential for drug discovery - Abdou, Moaz M.; O’Neill, Paul M.; Amigues, Eric; Matziari, Magdalini (Drug discovery today, 2019)
[Display omitted] •The rational design of phosphinic acids as medicinal agents towards a number of diseases.•The current status of the phosphinate based prodrugs and drug delivery systems.•The medicinal applications of phosphinates in the clinical stage.•The potential of phosphinic acids as therapeutics. Phosphinic acid derivatives exhibit diverse biological activities and a high degree of structural diversity, rendering them a versatile tool in the development of new medicinal agents. Pronounced recent progress, coupled with previous research findings, highlights the impact of this moiety in medicinal chemistry. Here, we highlight the most important breakthroughs made with phosphinates with a range of pharmacological activities against many diseases, including anti-inflammatory, anti-Alzheimer, antiparasitic, antihepatitis, antiproliferative, anti-influenza, anti-HIV, antimalarial, and antimicrobial agents. We also provide the current status of the corresponding prodrugs, drug-delivery systems, and drug applications of phosphinic acids in the clinical stage